Thermal Performance And Analysis of a Solar water Heating System With Heat Pipe Evacuated Tube Collector (International Journal of Food and Nutritional Sciences, 2023)
Abstract: Renewable energy is mostly used by many countries now days for energy generation and save our environment as well as save conventional fuel resources. Solar energy is one of the most efficient, clean and affordable energy alternatives available today. With the current concerns about global warming and ever-increasing energy rates, countries are seriously looking for domestic and industrial usage of solar energy. Cooling, refrigeration, and air conditioning processes are considered essential needs and major requirements for all human beings in our world today.